2017
DOI: 10.1371/journal.pone.0177787
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictors of oral cancer knowledge in a predominantly African American community

Abstract: PurposeTo characterize smoking and alcohol use, and to describe predictors of oral cancer knowledge among a predominantly African-American population.MethodsA cross-sectional study was conducted between September, 2013 among drag racers and fans in East St. Louis. Oral cancer knowledge was derived from combining questionnaire items to form knowledge score. Covariates examined included age, sex, race, marital status, education status, income level, insurance status, tobacco and alcohol use. Adjusted linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
(65 reference statements)
0
16
0
4
Order By: Relevance
“…Additional factors that could be contributing to the later presentation of black patients include mistrust toward the health care system, lower level of public awareness, and lower rates of dental care services and oral screening examinations. 22-25 To our knowledge, the effectiveness of an oral screening program implemented among a diverse racial/ethnic community has not been investigated. In addition, it is unclear if the lower rate of surgery treatment among blacks compared to the other racial/ethnic groups is a result of late presentation or other factors such as inappropriate treatment and patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors that could be contributing to the later presentation of black patients include mistrust toward the health care system, lower level of public awareness, and lower rates of dental care services and oral screening examinations. 22-25 To our knowledge, the effectiveness of an oral screening program implemented among a diverse racial/ethnic community has not been investigated. In addition, it is unclear if the lower rate of surgery treatment among blacks compared to the other racial/ethnic groups is a result of late presentation or other factors such as inappropriate treatment and patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that the objectives of the Healthy People 2020 initiative mentioned above will be reached at the current rate of increase in the diagnosis of late‐stage HNC. In the absence of a mortality benefit for asymptomatic mass screenings, as per the US Preventive Services Task Force oral cancer screening guideline, it is critical that there is sustained public awareness and education regarding the early detection of HNC, and prevention through cancer risk mitigation practices . This is particularly important because late‐stage disease often requires multimodality treatment and has a poorer prognosis than early‐stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…33 Patient awareness about oral cancer in particular has been shown to be poor in the United States and around the world. [34][35][36][37][38] A large observational study in India found that brochures about oral cancer including details about how to perform a mouth self-examination significantly increased awareness about oral cancer and its risk factors. 39 Another study in Florida found that a highway billboard campaign effectively increased awareness about oral cancer in surrounding communities.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to health literacy, more than one‐third of patients in the United States are estimated to have limited health literacy based on a task‐oriented assessment that was conducted on approximately 19 000 adults in 2003 33 . Patient awareness about oral cancer in particular has been shown to be poor in the United States and around the world 34‐38 . A large observational study in India found that brochures about oral cancer including details about how to perform a mouth self‐examination significantly increased awareness about oral cancer and its risk factors 39 .…”
Section: Discussionmentioning
confidence: 99%